Effectiveness of surface protection for resin-modified glass-ionomer materials - Ribeiro, Ana Paula Granato; Serra, Mônica Campos; Paulillo, Luís Alexandre M. S.; Rodrigues Jr., Antônio Luiz (My University, 1999)
Objective: The purpose of this study was to evaluate the effectiveness of various surface treatments for resin-modified glass-ionomer restorative materials by determining dye uptake spectrophotometrically. Method and materials: Two hundred twenty-four specimens, 4.1 mm in diameter and 2.0 mm thick, were made of 3 materials: Vitremer, Fuji II LC, and Photac-Fil Aplicap. Specimens were divided into 15 groups. The positive and negative control specimens remained unprotected, while the experimental specimens were protected with Heliobond light-activated bonding resin, Colorama nail varnish, or surface coatings indicated by the manufacturers of the glass-ionomer materials: Finishing Gloss for Vitremer, Fuji Varnish for Fuji II LC, and Ketac Glaze for Photac-Fil. The disks were immersed in 0.05% methylene blue for 24 hours except for the negative control group, which was immersed in deionized water. After 24 hours, the disks were removed, washed, and individually placed in 1 mL of 65% nitric acid for 24 hours. The solutions were centrifuged and the spectrophotometric absorbance was determined at 606 nm. The dye uptake was expressed in micrograms of dye per milliliter, and the results were analyzed with the Kruskal-Wallis test. Results: There were no differences in dye uptake among the 3 resin-modified glass-ionomer restorative materials; however, all of them required surface protection. Conclusion: The best surface protection for the 3 evaluated materials was obtained with Heliobond light-activated bonding resin.
Keywords: Dehydration; Hybrid material; Hydration; Resin-modified glass-ionomer material; Surface protection